Development of Conservation Factor for Different Moisture Status of Watersheds - Bhargav, K S; Singh, A; Bhattacharya, A K (Journal of Agricultural Engineering, 2006)
A proper assessment of runoff is crucial for developing plans for soil and water conservation programs. Conservation Factor approach is one of the methods of assessment of water yield on temporal scale from micro watershed by using readily available parameters. In this method, rainfall, land use, conservation measure, soil type and slope of the watershed are the input parameters. These attributes are numerically indexed by assessing their impact on runoff. There is a scope to incorporate a few more parameters like AMC and improve the modeling for assessing runoff or water yield values from micro watersheds. In this approach, the potential of a watershed in producing runoff and in causing soil loss is related to Conservation Factor (CF), which is a dimensionless number and is a function of land use, conservation measure, soil type and area of the watershed. Like in the Curve Number method, the Antecedent Moisture Condition of the watershed can be incorporated in the Conservation Factor method for daily runoff estimation giving a better result.